活化教育專業知識之教學實踐研究計畫 - 陳鏗任 (My University, 2019)
本計畫以兩學期的時間，考慮不同課程特性與過去兩年教學所遇之挑戰，活化教學策略，精進教育類課程的學習體驗，以達到活化師資培育教學的創新目標：1. 教育基礎課程（教育哲學）：導入學思達教學法培養師資生批判思考與表達自身教育理念，輔以數位閃示卡之使用強化師資生知識基礎。2. 教師專業課程（教育研究法、教育統計學）：運用翻轉教室，將研究所層級的方法基礎課程融入實務元素。3. 教育方法課程（學習與閱讀理解策略、差異化教學）：以小組合作與展演，輔以同儕回饋，培養師資生應用多元教學方法與學習策略之技能。計畫主持人共完成54之教學影片、在五門課程中導入四種創新教法，並於報告末提出五個重要的教學設計原則，提供未來教授教育學科的教師參考。應用此五項原則，可以有效活化教育專業知識，讓學理貼近專業實務。

My research project for teaching practices enabled myself taking actions towards several instructional innovations based on distinct course characteristics, previous challenges that I faced in my classrooms, and the common cores of the new “preservice teacher education curriculum guidelines” announced by the Ministry of Education. These innovations improve the quality of my teacher education courses in the following ways: 1. Educational Foundations (i.e. Philosophy of Education): To introduce the ShareStart teaching methodology that could enhance critical thinking and oral-expressions; To introduce digital flashcards that enhance students’ memory of these foundation courses. 2. Teacher Professionalism (i.e. Research Methods of Education & Educational Statistics): To flip the classroom and make these method courses akin to field experience and problem-solving. 3. Instructional Methods (i.e. Learning how to Learn & Differentiated Instruction): To embed group works, showcases, and peer reviews that could motivate students to apply diverse teaching and learning strategies in the future. I conclude five design principles based on my instructional practices, research, and reflections. Future instructors may leverage those design principles to create their own better educational experiences for college students.
Activating Teacher Education Courses through Improvement of Scholarship of Teaching and Learning
Keywords: 師資培育; 數位閃示卡; 學思達教學法; MOOCs; 翻轉教室; Teacher Education; Digital Flashcards; ShareStart (teaching methodology); MOOCs; Flipped Classroom